Prevalence of POE in UK higher education institutions. Issue 1 (13th April 2015) - Riley, Mike; Cotgrave, Alison; Kokkarinen, Noora
Abstract : Purpose: – The purpose of this paper is to identify the extent to which Post-occupancy evaluation (POE) is understood and applied within higher education institutions across the UK and identify users' perceptions of its efficacy. Design/methodology/approach: – A mixed methodology was applied to this research. Part one consisted of an online survey intended to generate an overview of the extent of POE use across the sector. The second phase, intended to develop greater insight and understanding of users' perceptions of POE, relied upon in-depth interviews with a smaller sample drawn those who had completed the survey in part one. Findings: – Differing models of POE are used within higher education institutions with varying degrees of complexity. Models exist that are based on standard structures and templates, whilst entirely bespoke options have been developed by some institutions. The work found that there is a clear preference for applying bespoke methods rather than standardised ones. Research limitations/implications: – The research is based on a sample of Directors of Estates (DOEs) from UK Universities. The conclusions relate specifically to that sector and context. The extent for broader generalisation is limited by the research sample. Practical implications: – The work shows that POE is understood to have differing purpose and effectiveness in individual Universities. As a result there has been a proliferation in the number of models developed and applied. This leads to the conclusion that more coherent and consistent understanding should be promoted within the sector. Social implications: – The work has implications for the effective management of university buildings to support user satisfaction. Originality/value: – This paper indicates that there is prevalence of applying POE processes in higher education institutions and that specific models have been developed for the sector. However, the extent to which the process is valued and understood is highly variable.